Soil Layers Properties of a Profile Developed on the Past Depositional Series on Merbabu Volcano Central Java Indonesia - Mohammad Nurcholis; Susila Herlambang; Sri Aminah Suwartikaningsih; Dian Fiantis; Dwi Fitri Yudiantoro (UNIVERSITY OF LAMPUNG, 2019)
A wide and deep soil profile (around 1200 cm) was observed at Ketep Park West Slope of Merbabu volcano Central Java, Indonesia to identify the soil morphology, physical and, chemical and mineralogical properties. Results showed that several soil development processes occurred in each volcanic deposits with different characteristics. Most soil layers met some of andic soil properties criteria such bulk density <0.9 g.cm-3, P retention of >85%, and (Alo + ½ Feo) >2.0%. A thin melanic material showing black color layer was found at the lower part of the soil profile, i.e. in depth from 726 to 798 cm. The dominant material in most soil layers is an allophane. Minerals in the sand fraction were dominated by labradorite and augite, with some layers were hypersthene and green hornblende.